ETNOMATEMATIKA PADA AKTIVITAS MASYARAKAT PETANI MADURA DI KRANJINGAN SUMBERSARI JEMBER SEBAGAI BAHAN AJAR LEMBAR PROYEK SISWA - Juhria, Siti Jamilatus; Hobri, Hobri; Oktavianingtyas, Ervin (Department of Mathematics Education , University of Jember, 2015)
Abstract.Ethnomathematics is a study in applied science which has a matter of interest in numbers which the operation contains of a truth and a certain rule. The application has been used in the life of cultural groups or social communities. This research aims to describe the activity of Ethnomathematic peasants with paddy as the commodity in KeranjinganMaduranese, in Sumbersari, Jember Regency. The research uses qualitative study which employs ethnographic approach. The researcher collects the field data by interviewing and observing, using triangulation technique –a collecting data technique from the same source with different technique. The subjects of this research are 6 peasants. The result shows that there is Mathematic activity within farming of KeranjinganMaduranese, in Sumbersari, Jember Regency. The research result obtains tools for organizing the seed in order which are called bellak and kencah. The Mathematic activities which have been observed are to count the amount of employees, seeds, and fertilizers based on the land and work time. The activities apply Mathematic proportion law. Keywords:Ethnomathematics, bellak, kencah, proportion, Maduranese farmer